2018
DOI: 10.1002/pds.4689
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy outcomes in women exposed to cancer chemotherapy

Abstract: Purpose: There is little data on the effects of cancer chemotherapy in pregnant women. The objective of this study was to describe pregnancy outcomes of women exposed to cancer chemotherapy, recorded in the French Terappel database. Methods:We performed a descriptive, prospective study of the pregnancies of women exposed to cancer chemotherapy recorded in Terappel between June 1984 and December 2016. Terappel is a French database that has recorded questions of health professionals and/or individuals at the Reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…9 However, we have some recent studies including one from oncology where outcomes seem slightly better than previously noted. [10][11][12][13][14][15] and we are actively exploring and using modalities to preserve fertility. This includes embryo/ oocyte cryopreservation or ovarian tissue cryopreservation.…”
Section: Introductionmentioning
confidence: 99%
“…9 However, we have some recent studies including one from oncology where outcomes seem slightly better than previously noted. [10][11][12][13][14][15] and we are actively exploring and using modalities to preserve fertility. This includes embryo/ oocyte cryopreservation or ovarian tissue cryopreservation.…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer (BC) is the most commonly diagnosed malignancy during pregnancy with an estimated incidence of one in 3000 pregnancies [1,2]. The incidence of cancer during pregnancy is expected to rise further in developed countries, due to an increase in the mean maternal age at pregnancy and to an increasing incidence of cancer in young patients throughout the last decade [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Data about the obstetrical and fetal safety of chemotherapy administered during pregnancy are still not conclusive [7,8]. Several studies have reported higher rates of neonatal complications after in utero exposure to anticancer drugs [1,2,9], whereas others have found no significant differences [10,11]. The unwanted effects of chemotherapy administered during pregnancy depend mainly on the gestational stage; exposure during the first trimester is associated with a 10-20% risk of fetal malformations, whereas exposure during the second and third trimesters is significantly safer, with a fetal malformation rate similar to the unexposed population [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 In previous studies, among 24 females who treated for Hodgkin's disease in childhood, 17patients (70.8%) had normal gonadal function with regular menstrual periods. 12 Besides, chemotherapy has a negative influence on pregnancy outcomes 13 and increases the incidence of neonatal neutropenia. 14 It was unclear whether subsequent childbearing would increase the mortality risk of women with carcinoma.…”
Section: Introductionmentioning
confidence: 99%